Hydride-dehydride fine zirconium powders for pyrotechnics - Amelichkin I. V. Ivan Vyacheslavovich; Knyazeva E. M. Elena Mikhailovna; Medvedev R. O. Rodion Olegovich; Muslimova A. V. Aleksandra; Nefedov R. A. Roman Andreevich; Orlov V. V. Vladislav Viktorovich; Sachkov V. I. Viktor Ivanovich; Sachkova A. S. Anna Sergeevna; Stepanova O. B. Oyuna Borisovna; Zhukov I. A. Iljya Aleksandrovich (2021, 2021)
Title screen